Effect of Additives on Some Physical Parameters of Palm Oil - N. O. Eddy; A. S. Ekop (E-Journal of Chemistry)
Effect of additives (carrot, lime, paw paw and red dye) on the density, viscosity, moisture content and melting point of palm oil (PO) was investigated by dissolving 1g of each additive to 10 mL of pre-analysed oil in a beaker. The mixture was heated and their their moisture content, melting point, viscosity and density were determined. The result of the analysis shows that all the additives significantly increased the density, moisture content and viscosity (except lime) of the oil. Addition of paw paw and red dye also increased the melting point of the oil while the addition of carrot and lime juice decreased the melting point of the oil.